ANALISIS DINAMIS PENERIMAAN PAJAK DAN PENGELUARAN PEMERINTAH TERHADAP GDP DI INDONESIA - reni, fhatahul arrazaq; Saputra, Putu Mahardika Adi (Journal of Development Economic and Social Studies, 2023)
This article aims to look at the effects of fiscal policy, tax revenues and government spending on GDP in Indonesia during the 2000-2022 period. By using the Vector Error Correction Model (VECM) method, it will be seen the response of GDP to shocks from fiscal policy. Through the impulse response function the effect of government spending and tax revenue on GDP is positive. For the size of the effect, the effect of tax revenue is greater than the effect of government spending on GDP.